Antimicrobial Potential of Ethanol Extract from Avocado Seeds (persea americana mill.) on The Healing of Socket Wounds from Tooth Extraction in Male Wistar Rat - Susanna Halim; Florenly Florenly; Rayvan Juan Gustian (Jurnal Penelitian Pendidikan IPA, 2026)
Healing of tooth socket wounds after tooth extraction is a complex process involving phases of inflammation, proliferation, and tissue remodeling. Avocado seeds (Persea Americana Mill.) are known to contain bioactive compounds, including flavonoids, saponins, tannins, and triterpenoids, which have the ability to accelerate the wound healing process. This study aims to determine the effectiveness of avocado seed ethanol extract gel on changes in body weight, socket wound diameter, and socket depth after tooth extraction. This study used a laboratory experimental design with a post-test only control group design using male Wistar rats as test animals. The samples were divided into five groups, consisting of a negative control, a positive control (Gengigel), and treatment groups with avocado seed ethanol extract gel at concentrations of 10%, 20%, and 30%. Body weight was measured from day 1 to day 14. The diameter and depth of the socket wound were also measured periodically. Data analysis used the Paired Samples T-Test, Welch ANOVA, and Dunnett T3 Posthoc test in accordance with the results of normality using the Shapiro-Wilk test and data homogeneity using the Levene test. Based on the results of the study, it was found that 10% ethanol extract gel from avocado seeds was most effective in maintaining the stability of the body weight parameters of the test animals, and 30% ethanol extract gel from avocado seeds was most effective in accelerating the reduction in wound diameter and depth, with results comparable to the gold standard (Gengigel). It can be concluded that ethanol extract gel from avocado seeds, especially at a concentration of 30%, is effective in accelerating the healing process of socket wounds after tooth extraction.